The domestic workers convention and its importance for member states of the European union - Τοπάλη, Πηνελόπη (The Greek Review of Social Research, 2014)
On 16 June 2011 the International Labour Organization adopted the Convention concerning decent work for domestic workers in an effort to set minimum labour standards for domestic workers and help professionalize domestic work worldwide. In the European Union, differences in domestic work regulations reflect socio-cultural differences on perspectives pertaining to migration, women, work and domestic space. The present article examines in a comparative manner state regulations of domestic work such as its definition, working hours, wages, in-kind payments, and conditions of work. At the same time, itevaluates the impact of the Convention on member states of the European Union and assessesits political and cultural importance.